Nipah Virus: An Emergent Deadly Paramyxovirus Infection In Bangladesh - Wahed, Farema; Kader, Syed Abdul; Nessa, Akhtarun; Mahamud, Md Mukti (Journal of Bangladesh Society of Physiologist, 2012)
Nipah virus, a member of the genus Henipavirus, a new class of virus in the Paramyxoviridae family, has drawn attention as an emerging zoonotic virus in south east and south asian region. Case fatality rate of Nipah virus infection ranges from 40-70% although it has been as high as 100% in some outbreaks. Many of the outbreaks were attributed to pigs consuming fruits partially eaten by fruit bats, and transmission of infection to humans. In Bangladesh, 7 outbreaks of Nipah virus infection were identified during the period 2001–2007. In Bangladesh, Nipah virus infection was associated with contact with a sick cow, consumption of fresh date palm sap (potentially contaminated with pteropid bat saliva), and person-to-person transmission. In the most recent epidemic at least 15 people died due to Nipah virus infection in Hatibandha, Lalmonirhat district in a remote northern Bangladesh town in 2011 adding to the previous death toll of 113 in the country . Human infections range from asymptomatic infection to fatal encephalitis. Infected people initially develop influenzalike symptoms of fever, headaches, myalgia , vomiting and sore throat. This can be followed by dizziness, drowsiness, altered consciousness, and neurological signs that indicate acute encephalitis. Some people can also experience atypical pneumonia and severe respiratory problems. The virus is detected by ELISA, PCR, immunofluoroscent assay and isolation by cell culture. Treatment is mostly symptomatic and supportive as the effect of antiviral drugs is not satisfactory, and an effective vaccine is yet to be developed. So the very high case fatality addresses the need for adequate and strict control and preventive measures. DOI: http://dx.doi.org/10.3329/jbsp.v6i2.9764 JBSP 2011 6(2): 134-139